Peran Mikrobiologi dalam Pengolahan Limbah Pertanian Menjadi Pupuk Organik - Tuti Ariani Bawamenewi; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Agricultural waste treatment is an organism that offers innovative solutions to reduce the negative environmental impact of waste while increasing agricultural productivity. By using microorganisms such as bacteria, fungi, and actinomycetes, wastes such as straw, manure, and coffee grounds can be effectively treated. This biological process accelerates the decomposition of organic matter into more benign substances and nutrients, such as nitrogen, phosphorus and potassium, which are essential for plant growth. In addition to improving soil fertility, the use of organic fertilizers also reduces dependence on chemical fertilizers, greenhouse gas emissions, and sustainable agriculture. The aim of this study was to investigate the role of microbiology in agricultural waste transformation by examining its mechanisms, potentials, and challenges. The results of this study show that microorganism-based technologies contribute to more environmentally friendly practices and reinforce fundamental economic principles. Processing agricultural waste into organic fertilizer is a strategic step in realizing sector sustainability.